A criminalização dos movimentos sociais no Brasil frente a lei antiterrorismo (lei 13.260/2016): avanço do estado punitivo e retração democrática - Muniz Filho, José Carlos Cunha (2021)
The constitution of a Punitive State in Brazil, with the criminalization of misery and mass incarcerations, has been verified by several national researchers. In such a reality, in which criminal mechanisms for social control and mitigation of conflicts caused by neoliberal social deterioration are widely used, democracy is increasingly degraded and the limits to the power to punish are obsolete. In this context, this study aims at understanding whether the Anti-Terrorism Law (Law 13.260/2016) presents itself as a mechanism for amplifying punishment, especially for the criminalization of social movements and the ensuing restrictions on the freedoms of demonstration and assembly. After a contextualization of the national political conjuncture and an examination of the fundamental rights from the guaranteeist perspective, the central object of this thesis is to analyze the Law 13.260/2016 itself, considering the current projects that intend to modify it at the National Congress. This study starts from the hypothesis that Law 13.260 / 2016 has been used for criminalizing social movements and that proposals for modifying it aims at radicalizing such criminalization. Moreover, by analyzing the Decree 9.527/2018, related to anti-terror legislation, this thesis also seeks to understand whether it can deepen the use of such law for curbing contesting organizations.